Acute immune thrombocytopenic purpura in childhood Presentation and treatment A Hospital based study - Al-Naddawi, Mahjoob; Ibraheem, Mohammad F.; Sharhan, Faraqid J. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Acute idiopathic thrombocytopenic purpura (ITP) is a self – limiting illness, usually occurring after an infectious disease, and it is due to decrease number of circulating platelets manifests as a bleeding tendency, easy bruising (purpura), or extravasations of blood from capillaries into skin and mucous membranes. Objective: To study and analyze the natural history of idiopathic thrombocytopenic purpura and treatment used in children below 15years. Patients and methods: A cross sectional descriptive study was carried on total of 72 patients their ages range between(1-15)years who were admitted to Children Welfare Teaching Hospital / Baghdad from 1st of July 2010 to30th of June 2011. Seventy two cases admitted during that period and diagnosed as acute immune thrombocytopenic purpura but bone marrow aspiration study was done in 57cases and those cases that were studied and were analyzed to all types of clinical presentation & management used. Results: Age group were ranged from (1-15) years with peak in age group of (1-5) years 38(66.7%), male were 29 (50.9%) equal to female 28 (49.1%). Most cases were reported in spring 25(43.9%), with preceding viral illness was encountered in 37 (64.9%) patients. Most cases were presented with skin rash 54(94.7%) except three cases, the epistaxis was the second presentation 21(36.9%), and the least presentations were intracranial hemorrhage & menorrhagia 1(1.8%). Most of the cases were treated with steroid (91.1%). Conclusions: Bone marrow exanimation is recommended in each case of the thrombocytopenia, and if decision of bone marrow exanimation is taken, it is essentially to do it prior to steroid therapy. Oral prednisolone is the readily available, inexpensive drug that can be taken orally in hospital and as outpatient. Methylprednisolone rapidly increases platelet counts so reduces period of hospitalization, but it is not always available and can be used as in patient treatment only.